Role of garlic in the prevention of ischemia-reperfusion injury - YEGEN, BERRAK (WILEY, 2007)
Garlic in different forms has antioxidant properties. These properties are shown to be due to the existence of compounds such as water soluble organosulfur compounds, S-allylcysteine and lipid soluble compounds like diallyl sulfide. The in vivo and in vitro ischemia reperfusion studies showed that prophylactic administration of aqueous garlic prior to ischemia reperfusion inhibit lipid peroxidation and prevent depletion in glutathione through its compounds that led to functional recovery. Its ability to inhibit neutrophil migration could suppress fibrosis formation. These preventive effects are seen in models that studied organs such as kidney and liver with functional recovery. Organ system specific activity such as angiotensin converting enzyme-inhibiting activity contributes to a cardioprotective and blood pressure lowering effect. Future studies should focus on post ischemia reperfusion administration of garlic to explore its rescue potential rather than prophylactic impact. Bench research findings should be translated into clinical use through human studies.
Keywords: garlic; ischemia; liver; oxidative damage; reperfusion; ISCHEMIA/REPERFUSION INJURY; OXIDATIVE STRESS; ENDOGENOUS ANTIOXIDANTS; RENAL DYSFUNCTION; HEART-DISEASE; TISSUE-INJURY; RISK-FACTORS; EXTRACT; RATS; MELATONIN